Effects of Bacterial Cellulose Nanocrystals on the Mechanical Properties of Resin-Modified Glass Ionomer Cements - Moradian, Marzieh; Nosrat Abadi, Mohsen; Jafarpour, Dana; Saadat, Maryam (European Journal of Dentistry, 2020)
Objectives The purpose of this study was to evaluate the effect of bacterial cellulose nanocrystals (BCNCs) on the mechanical properties of resin-modified glass ionomer cements (RMGICs) including compressive strength (CS), diametral tensile strength (DTS), and modulus of elasticity (E).Materials and Methods BCNCs were incorporated into RMGIC at various concentrations (0.3, 0.5, and 1 wt%). Unmodified RMGIC was used as the control group. The specimens were stored in distilled water at 37°C for 24 hours. CS and DTS, as well as modulus of elasticity, were evaluated using a universal testing machine. The nanostructure of BCNCs was observed via field emission scanning electron microscopy.Statistical Analysis One-way analysis of variance and post-hoc Tukey tests were used for data analysis. Level of significance was at p < 0.05.Results The addition of BCNCs to RMGIC led to an increase in all of the tested mechanical properties compared with the control group, with a significant increase observed for 1 wt% BCNC. CS and DTS improved up to 23%, and modulus of elasticity increased by 44%.Conclusions The addition of BCNCs to the RMGIC improved the mechanical properties, including CS, elastic modulus, and DTS. Thus, the newly developed RMGICs with BCNCs might represent an ideal and promising novel dental material in restorative dentistry.
Keywords: bacteria; cellulose; compressive strength; elastic modulus; glass ionomer cements; tensile strength